Pengaruh Kecerdasan Intelektual dan Kecerdasan Emosional terhadap Classroom Management Dengan Internal Locus of Control Sebagai Variabel Intervening (Studi Pada Guru SD Daerah Binaan 3 Koordinator Wilayah Kecamatan Tegal Barat) - Al Qusaeri, Norma Nur Shifa; Sunarto, Sunarto (LP. Ma'arif Janggan Magetan, 2024)
This study aims to research and analyze the impact of cognitive intelligence and emotional intelligence on internal control, as well as the impact of cognitive intelligence, emotional intelligence, and internal control on classroom management. The subjects of the study consisted of elementary school teachers in Region 3, West Tegal District, Tegal City, with a total of 80 respondents. The sampling method used is the Saturated Sampling Technique, where the entire population is sampled. Data collection was carried out through questionnaires, and data analysis using regression tests with mediation techniques. The results showed that cognitive intelligence has a positive impact on internal control, as well as emotional intelligence. However, cognitive intelligence does not have a significant impact on classroom management. On the other hand, emotional intelligence has a positive impact on classroom management. Internal control also has a positive impact on classroom management, and acts as a mediator in the relationship between cognitive intelligence and classroom management.